Zonificación agroecológica y plan del uso del suelo para la zona de riego del sistema Santiago. - González Zúñiga, Janio Enrique (2016)
The present work started in the month of April of 2017, having as scenario the irrigation area of the Santiago system, located in the Canton and Province of Loja. Based on existing secondary information and through the generation of new information, a land use plan for the irrigation area was proposed, using all the tools of the GIS (Geographic Information Systems). The first thing to be done was the collection of information, the sampling that was carried out in the whole irrigation area, which allowed to make the integral diagnosis to later elaborate the land use plan, the variables analyzed were: depth, texture, pH, slope, temperature, precipitation, coverage, current land use and road network); At the same time was made an agro productive diagnosis. In the second stage, the information processing was carried out, generating the agro ecological zoning of the irrigation area, which was used to prepare the land use plan, through the following methodological process: identification of potential use or preliminary zoning in based on the soil potential, slopes, depth, texture and pH of the soil. Subsequently, the current use of the soil was evaluated, through the analysis of the vegetation cover through aerial photos and field supervision, to intercept then with the potential use of the soil and obtain the conflicts of use. With the help of aerial photos, also was analyzed the accessibility of the irrigation area, was intercepted this variable with conflicts of use and current use, obtaining finally the agro ecological zoning, with the interpretation of what was obtained, the map of areas of use was generated and the land use plan. From this resulting zoning were obtained four land use zones: 1. Potential development zone for the production of vegetables, 2. Development Agrosilvopastoril zone, 3. Potential development zone for fruit production and 4. Protection and conservation zone. From these zones, four projects were formulated, immersed in the proposal for the improvement of agricultural production.